Distribution of Abundant and Active Planktonic Ciliates in Coastal and Slope Waters Off New England - Tucker, Sarah J.; McManus, George B.; Katz, Laura A.; Grattepanche, Jean-David (Frontiers in Microbiology, 2017)
Despite their important role of linking microbial and classic marine food webs, data on biogeographical patterns of microbial eukaryotic grazers are limited, and even fewer studies have used molecular tools to assess active (i.e. those expressing genes) community members. Marine ciliate diversity is believed to be greatest at the chlorophyll maximum, where there is an abundance of autotrophic prey, and is often assumed to decline with depth. Here, we assess the abundant (DNA) and active (RNA) marine ciliate communities throughout the water column at two stations off the New England coast (Northwest Atlantic) – a coastal station 43 km from shore (40m depth) and a slope station 135 km off shore (1000m). We analyze ciliate communities using a DNA fingerprinting technique, Denaturing Gradient Gel Electrophoresis (DGGE), which captures patterns of abundant community members. We compare estimates of ciliate communities from SSU-rDNA (abundant) and SSU-rRNA (active) and find complex patterns throughout the water column, including many active lineages below the photic zone. Our analyses reveal 1) a number of widely-distributed taxa that are both abundant and active; 2) considerable heterogeneity in patterns of presence/absence of taxa in offshore samples taken 50 meters apart throughout the water column; and 3) three distinct ciliate assemblages based on position from shore and depth. Analysis of active (RNA) taxa uncovers biodiversity hidden to traditional DNA-based approaches (e.g. clone library, rDNA amplicon studies).